Developing Team Design Patterns for Hybrid Intelligence Systems - Van Zoelen, Emma; Mioch, Tina; Tajaddini, Mani; Fleiner, Christian; Tsaneva, Stefani; Camin, Pietro; Gouvêa, Thiago S.; Baraka, Kim; De Boer, Maaike H. T.; Neerincx, Mark (HHAI 2023: Augmenting Human Intellect, 2023)
With artificial intelligence (AI) systems entering our working and leisure environments with increasing adaptation and learning capabilities, new opportunities arise for developing hybrid (human-AI) intelligence (HI) systems, comprising new ways of collaboration. However, there is not yet a structured way of specifying design solutions of collaboration for hybrid intelligence (HI) systems and there is a lack of best practices shared across application domains. We address this gap by investigating the generalization of specific design solutions into design patterns that can be shared and applied in different contexts. We present a human-centered bottom-up approach for the specification of design solutions and their abstraction into team design patterns. We apply the proposed approach for 4 concrete HI use cases and show the successful extraction of team design patterns that are generalizable, providing re-usable design components across various domains. This work advances previous research on team design patterns and designing applications of HI system
Keywords: Hybrid Intelligence; Team Design Patterns; Use-case based research; Human-centered AI; Co-evolution; Interdependence

Ensuring a Robust Multimodal Conversational User Interface during Maintenance Work - Fleiner, Christian; Riedel, Till; Beigl, Michael; Ruoff, Marcel (ACM International Conference Proceeding Series, 2021)
It has been shown that the provision of a conversational user interface proves beneficial in many domains. But, there are still many challenges when applied in production areas, e.g. as part of a virtual assistant to support workers in knowledge-intensive maintenance work. Regarding input modalities, touchscreens are failure-prone in wet environments and the quality of voice recognition is negatively affected by ambient noise. Augmenting a symmetric text- and voice-based user interface with gestural input poses a good solution to provide both efficiency and a robust communication. This paper contributes to this research area by providing results on the application of appropriate head and one-hand gestures during maintenance work. We conducted an elicitation study with 20 participants and present a gesture set as its outcome. To facilitate the gesture development and integration for application designers, a classification model for head gestures and one for one-hand gestures were developed. Additionally, a proof-of-concept for operators' acceptance regarding a multimodal conversational user interface with support of gestural input during maintenance work was demonstrated. It encompasses two usability testings with 18 participants in different realistic, but controlled settings: notebook repair (SUS: 82.1) and cutter head maintenance (SUS: 82.7).
CRIS-Team Scopus Importer:2021-10-01
Keywords: Assistance systems; conversational agent; elicitation study; industry 4.0; multimodal interface; task guidance; user-defined gestures

Leveraging Human-Agent Collaboration for Multimodal Task Guidance with Concurrent Authoring Capabilities - Fleiner, Christian (IUI '22 Companion: 27th International Conference on Intelligent User Interfaces, 2022)
Instructive assistance systems are applied to assist users in performing a task by providing instructions. These systems are especially relevant for industrial workers and service technicians who must cope with the increasing task variety and complexity that resulted from the trend of applying cyber-physical production systems and small lot sizes. While current research mainly focuses on assembly work and the application of augmented reality, there is a lack of research for these systems for adapting to the challenging conditions of maintenance environments and for providing concurrent authoring capabilities. Within this PhD project, we aim to design a multimodal conversational agent as an instructive assistance system with authoring capabilities and evaluate the system in three different scenarios to close this research gap.<br
Keywords: augmented reality; content authoring; conversational agent; hybrid intelligence; multimodal interface; industry 4.0; task guidance; web of things; Assistance systems

RDeF: Prosuming Interactive Stories to Train RDF and SPARQL - Fleiner, Christian; Grümmer, Julian; Zvekan, Goran (ITiCSE ’22: Proceedings of the 27th ACM Conference on Innovation and Technology in Computer Science Education Vol. 2, 2022)
Traditional database courses mainly focus on managing relational databases, but understanding NoSQL databases is becoming more relevant to computer science students. This also applies to Linked Data with the standards RDF and SPARQL where training material is scarce. Scarcity can be countered by involving students in the creation process. This paper introduces RDeF - - an open-source prosumer framework where students can consume and produce interactive stories to train their RDF and SPARQL skills. Stories are composed of scenes that are created with RDF triples from templates. Within stories, players must identify hidden RDF triples to build the knowledge base and query it by executing SPARQL requests to answer questions.
CRIS-Team Scopus Importer:2022-08-05
Keywords: linked data; educational game; knowledge graph; semantic web; prosumer; student generated content

WireGraph - Entwicklung eines Lernspiels mit Prosumentenumgebung zur Förderung der fachlichen und digitalen Kompetenz von Wirtschaftsstudierenden - Fleiner, Christian; Grümmer, Julian; Zvekan, Goran; Harth, Andreas (INFORMATIK 2021 - Computer Science & Sustainability, 2021)
Die Europäische Kommission warnt davor, dass die Entwicklung der Digitalisierung unzureichend in der Hochschullehre beachtet wird. Vielen Absolventen:innen mangelt es an digitaler Kompetenz. Dem steht gegenüber, dass die digitalen Anforderungen auf dem Arbeitsmarkt stetig wachsen. Dies gilt auch für Berufe des Finanzbereichs. Um die Vermittlung von digitaler Kompetenz in die Lehre miteinzubinden, eignet sich das von der Europäischen Kommission vorgeschlagene Referenzmodell der digitalen Kompetenz. Es besteht allerdings ein großer Forschungsbedarf, wie das Referenzmodell explizit in die Lehre übertragen werden kann. In diesem Beitrag wird das Konzept des Lernspiels WireGraph vorgestellt, mit dem Studierende der Wirtschaftswissenschaften die Arbeit mit Wissensgraphen erlernen, um den Wirecard-Skandal aufzuarbeiten. Dazu wird eine Prosumentenumgebung gestellt, mit der der Kompetenzbereich Erstellung digitaler Inhalte des Referenzmodells vollständig und über alle Leistungsniveaus hinweg vermittelt wird. Dabei erlernen Studierende nicht nur die Grundlagen von RDF und SPARQL, sondern können diese auch gezielt für ihre Ideen und weiteres Fachwissen einsetzen.<br
CRIS-Team Scopus Importer:2024-12-16
Keywords: Audit; Big Data; DigComp; Digitalisierung; Educational Game; Interaktive Lehre; Linked Data; Prosument; Wissensgraph; Wirecard

WireGraph - Entwicklung eines Lernspiels mit Prosumentenumgebung zur Förderung der fachlichen und digitalen Kompetenz von Wirtschaftsstudierenden - Fleiner, Christian; Grümmer, Julian; Zvekan, Goran; Harth, Andreas (INFORMATIK 2021 Computer Science & Sustainability, 2021)
Die Europäische Kommission warnt davor, dass die Entwicklung der Digitalisierung unzureichend in der Hochschullehre beachtet wird. Vielen Absolventen:innen mangelt es an digitaler Kompetenz. Dem steht gegenüber, dass die digitalen Anforderungen auf dem Arbeitsmarkt stetig wachsen. Dies gilt auch für Berufe des Finanzbereichs. Um die Vermittlung von digitaler Kompetenz in die Lehre miteinzubinden, eignet sich das von der Europäischen Kommission vorgeschlagene Referenzmodell der digitalen Kompetenz. Es besteht allerdings ein großer Forschungsbedarf, wie das Referenzmodell explizit in die Lehre übertragen werden kann. In diesem Beitrag wird das Konzept des Lernspiels WireGraph vorgestellt, mit dem Studierende der Wirtschaftswissenschaften die Arbeit mit Wissensgraphen erlernen, um den Wirecard-Skandal aufzuarbeiten. Dazu wird eine Prosumentenumgebung gestellt, mit der der Kompetenzbereich Erstellung digitaler Inhalte des Referenzmodells vollständig und über alle Leistungsniveaus hinweg vermittelt wird. Dabei erlernen Studierende nicht nur die Grundlagen von RDF und SPARQL, sondern können diese auch gezielt für ihre Ideen und weiteres Fachwissen einsetzen.<br
Keywords: Audit; Big Data; DigComp; Digitalisierung; Educational Game; Interaktive Lehre; Linked Data; Prosument; Wissensgraph; Wirecard